Association between COMT Val158Met and psychiatric disorders: A comprehensive meta‐analysis. Issue 2 (13th June 2017) - Taylor, Steven
Abstract : Catechol‐O‐methyltransferase (COMT) Val158Met is widely regarded as potentially important for understanding the genetic etiology of many different psychiatric disorders. The present study appears to be the first comprehensive meta‐analysis of COMT genetic association studies to cover all psychiatric disorders for which there were available data, published in any language, and with an emphasis on investigating disorder subtypes (defined clinically or by demographic or other variables). Studies were included if they reported one or more datasets (i.e., some studies examined more than one clinical group) in which there were sufficient information to compute effect sizes. A total of 363 datasets were included, consisting of 56, 998 cases and 74, 668 healthy controls from case control studies, and 2, 547 trios from family based studies. Fifteen disorders were included. Attention‐deficit hyperactivity disorder and panic disorder were associated with the Val allele for Caucasian samples. Substance‐use disorder, defined by DSM‐IV criteria, was associated with the Val allele for Asian samples. Bipolar disorder was associated with the Met allele in Asian samples. Obsessive‐compulsive disorder tended to be associated with the Met allele only for males. There was suggestive evidence that the Met allele is associated with an earlier age of onset of schizophrenia. Results suggest pleiotropy and underscore the importance of examining subgroups—defined by variables such as age of onset, sex, ethnicity, and diagnostic system—rather than examining disorders as monolithic constructs.